Portable Air Cleaner Usage and Particulate Matter Exposure Reduction in an Environmental Justice Community: A Pilot Study - Alina M McIntyre; Madeleine K Scammell; Patrick L Kinney; Kiran Khosla; Layne Benton; Roseann Bongiovanni; Jessica McCannon; Chad W Milando (SAGE Publishing, 2024)
Particulate matter (PM) exposure is associated with adverse health outcomes, including respiratory illness. A large fraction of exposure to airborne contaminants occurs in the home. This study, conducted over 5 months in a community with high asthma rates (Chelsea, MA, USA), investigated the use of portable air cleaners (PACs) to reduce indoor PM. Seven asthma-affected households participated, receiving a PAC (Austin Air Health Mate HEPA filter), a QuantAQ sensor to measure PM 1 , PM 2.5 , PM 10 (µg/m 3 ), and a HOBO plug-load data logger to track PAC usage. Results describe hourly and daily PM concentrations and PAC usage for each household. Hourly average PM concentrations decreased when PACs were turned on (vs. when they were turned off) across households during the study period: PM 1 decreased by 0.46 µg/m 3 , PM 2.5 decreased by 0.69 µg/m 3 , and PM 10 decreased by 3.22 µg/m 3 . PAC usage varied for each household, including constant usage in one household and only usage at certain times of day in others. Higher filtration settings led to lower PM, with significant reductions in some, but not all, homes. Our findings highlight some difficulties in implementing household PAC interventions, yet also provide evidence to support household-level interventions to reduce PM and other indoor sources of air pollution. We also highlight academic-community partnerships as contributing to evidence-based solutions.